Argentina and Spain: Argentinean youth and Physical Culture representations in No-Do images - Galak, Eduardo (Historia y Memoria de la Educación, 2020)
The aim of this article is to analyze the uses of documentary informative cinema as a cultural artifact which was employed as a pedagogical device. To do so, we studied motion pictures filmed in Argentina and shown in Spain in the second quarter of the 20th century, in an attempt to understand how a symmetrical aesthetic is shaped to narrate the bodily practices of youth. Informative documentary cinema, especially newsreels, constituted a resource for mass communications. A familiarity can be observed between the Argentinean images analyzed between 1938-1955 in Sucesos Argentinos, with others made in the second quarter of the 20th century in Spain, through No-Do. In addition to economic, political and cultural influences, Argentina imported into Spain ways of narrating state-organized physical culture. Sheltered in a nationalist rhetoric characteristic of the interwar period and the Second World War, it can be affirmed that there was a transnational aesthetic of how to narrate correct corporal and cultural comportment. Through images that were projected in theaters in these countries, newsreel broadcasts simultaneously and homogeneously transmitted the same discourse –everything, to everyone, at the same time–, resulting in a true transnational pedagogy. In short, a pedagogy outside the school walls is studied through informative documentary film images from the second quarter of the 20th century that aimed to form bodies and sensibilities.